2018
DOI: 10.1039/c8nr04971h
|View full text |Cite
|
Sign up to set email alerts
|

A flexible SERS-active film for studying the effect of non-metallic nanostructures on Raman enhancement

Abstract: Since the discovery of surface enhanced Raman scattering (SERS), the choice of SERS-active materials has been limited mainly to metals, especially gold and silver in the visible spectrum. Although non-metals can also be SERS-active by forming nanostructures or composite structures with SERS-active materials, the mechanism behind it is still unclear and there is no perfect technique to study it. In this work, by constructing a SERS structure on a flexible polydimethylsiloxane film, we provide a way to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…It has been demonstrated that 4-aminothiophenol (4-ATP) could be oxidized to p,p'-dimercaptoazobenzene (DMAB) on silver surface under light illumination. As known, plasmonic nanostructure can lead to an extremely localized electromagnetic field [79,111,112], which could result to an enhancement of Raman scattering, also called as surface-enhanced Raman scattering (SERS) [113]. SERS spectroscopy could be employed for effective identification of chemical reactions.…”
Section: -Atp To Dmab Conversionmentioning
confidence: 99%
“…It has been demonstrated that 4-aminothiophenol (4-ATP) could be oxidized to p,p'-dimercaptoazobenzene (DMAB) on silver surface under light illumination. As known, plasmonic nanostructure can lead to an extremely localized electromagnetic field [79,111,112], which could result to an enhancement of Raman scattering, also called as surface-enhanced Raman scattering (SERS) [113]. SERS spectroscopy could be employed for effective identification of chemical reactions.…”
Section: -Atp To Dmab Conversionmentioning
confidence: 99%
“…These properties are highly dependent on the chemical composition, size, shape and surface state of the nanocrystals . Therefore, controlled synthesis of nanocrystals is becoming a hot topic in many fields, and lots of efforts have been made to precisely control the morphology and surface state of the nanocrystals . Among various shaped nanocrystals, the sheet‐like ones show promising properties and applications due to their structural simplicity, large surface area, easy charge separation, etc .…”
Section: Figurementioning
confidence: 99%
“…The Raman enhancement could be further increased by extending the immersion period in AuNPs colloid or re‐adsorbing another layer of nanoparticles. The average enhancement factor (EF) was calculated (The details of the EF calculation was already described in our previous report) as 2.2×10 5 for the Raman band of PATP (typical spectrum shown in Figure c) at 1076 cm −1 , by using this equation EF=(normalISERS/normalIbulk)·(normalNbulk/normalNSERS) , whereas Nnormalbnormalunormallnormalk and NnormalSnormalEnormalRnormalS represent the number of excited molecules in bulk Raman and SERS measurements respectively, and Inormalbnormalunormallnormalk and InormalSnormalEnormalRnormalS represent the Raman intensities in bulk and SERS measurements respectively. This EF is slightly smaller than the reported one, which is probably due to the limited width of the line pattern.…”
Section: Figurementioning
confidence: 99%